Efecto de niveles de agua en el suelo sobre el crecimiento y desarrollo de palmas de vivero - Burgos S., Constanza; Perdomo R., Rodrigo; Cayón S., Daniel G. (Palmas, 2007)
The effect of different levels of soil moisture (saturation point 0 Mpa, medium water content -0,01 Mpa, field capacity -0,03 Mpa and water deficit -0,3 Mpa) on the growth and development of nursery palms was analyzed. Height, leaf emission rate, leaf area and dry matter variables of the palms were higher under soil medium moisture content conditions. Prolonged water deficit drastically affected the growth and development of roots and above-ground parts of the palms. The distribution of dry matter at different levels of soil moisture remained constant, which indicates that, even under water stress conditions, the biomass is distributed among plant parts in accordance with a defined growth pattern that favors either the roots or the above ground parts of the plant, depending on its development stage. At high levels of soil moisture, the leaf area ratio was higher during the initial growth stages and declined slightly as the plant's total dry weight increased, while at the lower levels of soil moisture, the leaf area ratio remained constant